Maternal Risk Factors Associated with Antepartum Stillbirth - Sara Raimondi; Valentina Massa; Claudia Ravaldi; Alfredo Vannacci; Gaetano Bulfamante; Anna Maria Marconi; Laura Avagliano (IMR Press, 2022)
Background: Stillbirth is a worldwide devastating adverse pregnancy outcome and specific maternal conditions have been associated with an increased risk of fetal death. However, despite the worldwide increased efforts in prevention of stillbirth, little improvements have been achieved in recent years. Our aim was to explore the role of maternal conditions that can be ascertained at the beginning of pregnancy (i.e., demographic and medical conditions/diseases) and estimate their contribution to antepartum stillbirth. An early identification of risk factors could offer to high-risk pregnancies a tailored antenatal surveillance by trained staff leading to a potential reduction of stillbirth rates. Methods: Retrospective case-control study in singleton pregnancies. The difference between fetal survival rates in women with or without risk factors was evaluated. Results: Antepartum stillbirth occurs more frequently in infertile, older women, with systemic diseases. Maternal conditions may affect fetal outcome in a time-dependent manner. Subdividing cases in early stillbirths (before 28 weeks of gestation) and late stillbirth (≥28 weeks of gestation) we observed that early stillbirths are associated with assisted reproductive technologies (Odds Ratio (OR) 3.10; 95% Confidence Interval (CI) 1.43-6.71), maternal age above 35 years (OR 1.59; 95% CI 1.17-2.17) and pre-gestational hypertension (OR 3.68; 95% CI 1.28-10.56). Autoimmune disease (OR 6.55; 95% CI 2.90-14.80), inherited thrombophilia (OR 2.94; 95% CI 1.40-6.18) and pre-gestational diabetes (OR 7.57; 95% CI 2.17-26.35) are independent risk factors for late stillbirths. Further, the risk of stillbirth rises with the increasing of the number of pathological maternal clinical conditions, reaching an OR of 5.27 (95% CI 2.32-11.98) in cases of mother with three or more conditions/diseases. Conclusions: Early awareness of the maternal conditions/diseases addressable at the beginning of pregnancy is crucial to offer a personalized plan for high quality care during gestation; for the prevention of stillbirth, a cared clinical management should acknowledge that pregnancies can be affected more severely and earlier as the number of abnormal maternal conditions increases.